2018
DOI: 10.1007/s00429-018-1713-2
|View full text |Cite
|
Sign up to set email alerts
|

Visual loss alters multisensory face maps in humans

Abstract: Topographically organised responses to visual and tactile stimulation are aligned in the ventral intraparietal cortex. The critical biological importance of this region, which is thought to mediate visually guided defensive movements of the head and upper body, suggests that these maps might be hardwired from birth. Here, we investigated whether visual experience is necessary for the creation and positioning of these maps by assessing the representation of tactile stimulation in congenitally and totally blind … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Despite these anatomical changes, visual experience is not necessary for the development of topographically organized maps of the face in the intraparietal cortex (Pasqualotto et al, 2018), or for the ability to represent the work space (Nelson et al, 2018). CB can form mental representations of the work space via haptic information as efficiently as sighted people, indicating that this ability does not depend on visual experience (Nelson et al, 2018).…”
Section: Sensory Deprivation Brain Plasticity Amodality and Spatialmentioning
confidence: 99%
“…Despite these anatomical changes, visual experience is not necessary for the development of topographically organized maps of the face in the intraparietal cortex (Pasqualotto et al, 2018), or for the ability to represent the work space (Nelson et al, 2018). CB can form mental representations of the work space via haptic information as efficiently as sighted people, indicating that this ability does not depend on visual experience (Nelson et al, 2018).…”
Section: Sensory Deprivation Brain Plasticity Amodality and Spatialmentioning
confidence: 99%
“…In support of this hypothesis Gori and colleagues (2012) showed that haptic orientation discrimination performance is impaired in blind children because vision could not calibrate touch on this task (Gori, Tinelli, Sandini, Cioni, & Burr, 2012). Indeed, several other studies demonstrated that perceptual functioning in the remaining senses of blind individuals is severely compromised Cappagli, Finocchietti, Baud-Bovy, Cocchi, & Gori, 2017;Vercillo, Burr, & Gori, 2016;Zwiers, Van Opstal, & Cruysberg, 2001) when accurate performance depends on high resolution visual input (Coluccia, Mammarella, & Cornoldi, 2009;Gori, Sandini, Martinoli, & Burr, 2014;Pasqualotto et al, 2018;Pasqualotto & Proulx, 2012;Vercillo et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
“…A key method to discover the importance of early sensory input for perceptual development is to compare those who have had a sense, such as vision, impaired at an early developmental stage to those who acquire sensory deprivation later in life. For example, comparing humans who became blind early in life to those who became blind at older ages has revealed the impact of visual experience during development on other aspects of perception and cognition (Bedny et al, 2012;Pasqualotto, Furlan, Proulx, & Sereno, 2018;Wan et al, 2010a, see Scheller, Petrini, & Proulx, 2018 for a review). Reports on early blind individuals with extraordinary auditory or tactile abilities have nurtured the idea that non-visual perceptual mechanisms improve in order to compensate for the lack of visual information (Goldreich & Kanics, 2003;Gougoux et al, 2004a;Kolarik, Cirstea, & Pardhan, 2013;Norman & Bartholomew, 2011;Röder et al, 1999;Vercillo, Milne, Gori, & Goodale, 2015;Voss et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…A key method to discover the importance of early sensory input for perceptual development is to compare those who have had a sense, such as vision, impaired at an early developmental age to those who acquire sensory deprivation later in life. For example, comparing humans who became blind early in life to those who became blind at older ages has revealed the impact of visual experience during development on other aspects of perception and cognition (Bedny, Pascual‐Leone, Dravida, & Saxe, 2012; Pasqualotto, Furlan, Proulx, & Sereno, 2018; Wan, Wood, Reutens, & Wilson, 2010, see Scheller, Petrini, & Proulx, 2018 for a review). Reports on early‐blind individuals with extraordinary auditory or tactile abilities have nurtured the idea that non‐visual perceptual mechanisms improve in order to compensate for the lack of visual information (Goldreich & Kanics, 2003; Gougoux et al., 2004; Kolarik, Cirstea, & Pardhan, 2013; Norman & Bartholomew, 2011; Röder et al., 1999; Vercillo, Milne, Gori, & Goodale, 2015; Voss et al., 2004).…”
Section: Introductionmentioning
confidence: 99%
“…those who became blind at older ages has revealed the impact of visual experience during development on other aspects of perception and cognition (Bedny, Pascual-Leone, Dravida, & Saxe, 2012;Pasqualotto, Furlan, Proulx, & Sereno, 2018;Wan, Wood, Reutens, & Wilson, 2010, see Scheller, Petrini, & Proulx, 2018 for a review).…”
mentioning
confidence: 99%